Mothers’ parenting patterns on stunting cases in toddlers: A case from Cirebon Health Center, West Java, Indonesia - Suhaeni, Eni; Azmii, Salman Nur; Ulfah, Siti Maria; Pratamawati, Tiar Masykuroh (GHMJ (Global Health Management Journal), 2024)
Background: A recent survey conducted in 2021 noted a high stunting incident was found in Cirebon, West Java of Indonesia, reached to 30.6%, even higher compare to the provincial rate (24.5%).  It has been known that parenting patterns and nutritional status are greatly influenced by the mother's understanding of managing health and nutrition for their baby in order to lower the stunting case. Aims: This study is to analyze the association between mother's parenting patterns and stunting in toddlers age 24-48 month in Cirebon Municipality. Methods: A total of 68 mothers have been selected using the consecutive sampling from a health facility in Cirebon City, Indonesia. This research uses survey and descriptive methods with a quantitative approach to examine the impact of mother's parenting patterns on stunting incidence in toddlers aged 24-48 months. This research also uses secondary data in the form of KIA (Mother and Child Health) records to identify the stunting cases among the respondents. Statistical analysis was employed to find how significant the variables affecting to the others. Results: From the questionnaire, it was found that the majority of participants were mothers aged 26-35 years old, and only graduated from high school or lower, and most of them were not working mothers. The stunting incidence found in this health center reached to 58.8 %. While only 36.8% of mothers exhibits well parenting pattern, the majority may show sufficient level (52.9%). Even only 10.3% of respondents correspond with low parenting pattern, however all of them found with stunting incidence. From statistical analysis, it is noted that mothers’ parenting pattern significantly affecting stunting cases in toddlers (p value = 0.001). Conclusion: This recent study concludes that parenting pattern significantly contributes to the number of stunting cases in toddler aged 24-48 months. The statistical analysis found mothers with well parenting pattern lower chance of having a stunted child. The data highlights the importance of knowledge and attitude will benefit in reducing the total number of stunted children in Cirebon city, Indonesia.   Keywords: Parenting pattern; Stunting; Mothers; Toddlers; Indonesia. Received: 09 November 2023, Reviewed: 19 November 2023, Revised: 06 January 2024, Accepted: 03 June 2024.